2023
DOI: 10.1186/s13052-023-01506-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of luteinizing hormone urinary levels in the diagnostic and therapeutic management of female central precocious puberty

Ilaria Brambilla,
Carmen Guarracino,
Carmelo Pistone
et al.

Abstract: Background Diagnosing central precocious puberty (CPP) requires an integrated approach based on clinical, biochemical and instrumental data. The diagnostic gold standard is represented by GnRH (gonadotropin-releasing hormone) stimulation test. Some undoubted limitations of this procedure led the international scientific community to look for cheaper and less invasive alternative diagnostic methods, such as luteinizing hormone urinary levels (uLH) measurement. This study aims to define the relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…and greater G.D., which reflects greater gonadal maturity unrelated to gonadotropins. The results of this study appear to be inconsistent with what is indicated by Pawlina and Ross (2015), who point out that the maturation of the sexual organs, both internal and external, during puberty is mediated by estrogens (steroids) promoted by gonadotropins, which foster the maturation of follicles (Brambilla et al 2023;Gea et al 2023). According to Villanueva and de Roux (2016) and Dickerson et al (2011) the main indicator of puberty is given by the increase in gonadotropin secretion, just before the onset of SSCs, which coincides with the onset of puberty and gonadal maturity (Micangeli et al 2023).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…and greater G.D., which reflects greater gonadal maturity unrelated to gonadotropins. The results of this study appear to be inconsistent with what is indicated by Pawlina and Ross (2015), who point out that the maturation of the sexual organs, both internal and external, during puberty is mediated by estrogens (steroids) promoted by gonadotropins, which foster the maturation of follicles (Brambilla et al 2023;Gea et al 2023). According to Villanueva and de Roux (2016) and Dickerson et al (2011) the main indicator of puberty is given by the increase in gonadotropin secretion, just before the onset of SSCs, which coincides with the onset of puberty and gonadal maturity (Micangeli et al 2023).…”
Section: Discussioncontrasting
confidence: 99%
“…As early puberty signals, gonadotropin-releasing hormones (GnRH) promote the release of lutropin (LH) and follitropin (FSH), which incite the production of sex steroid hormones and stimulate sexual maturation (Abdelaziz 2023;Fanis et al 2023). The pulsatile increase in LH and FSH indicates the characteristic biological signs of pubertal maturation (Léger and Carel 2016;Brambilla et al 2023), as the advent of secondary sexual characteristics (SSC) (Chotipakornkul et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation